The world keeps ending, and the world goes on - Choi, Franny (Ecco, an imprint of HarperCollinsPublishers, 2022)
"Many have called our time dystopian. But The World Keeps Ending, and the World Goes On reminds us that apocalypse has already come in myriad ways for marginalized peoples. With lyric and tonal dexterity, these poems spin backwards and forwards in time--from Korean comfort women during World War II, to the precipice of climate crisis, to children wandering a museum in the future. They explore narrative distances and queer linearity, investigating on microscopic scales before soaring towards the universal. Wrestling with the griefs and distances of this apocalyptic world, Choi also imagines what togetherness--between Black and Asian and other marginalized communities, between living organisms, between children of calamity and conquest--could look like. Bringing together Choi's signature speculative imagination with even greater musicality than her previous work, The World Keeps Ending, and the World Goes On ultimately charts new paths toward hope""--Front dust jacket flap.